PENDAMPINGAN GURU DALAM PENGELOLAAN PEMBELAJARAN MATEMATIKA BERBASIS ARTIFICIAL INTELLIGENCE DENGAN PENDEKATAN ADMINISTRASI PENDIDIKAN MODERN - N Noviyanti; Dwi Adhinda Junaidi Putri; Kiki Fajariani (LPPM Universitas Nusa Mandiri, 2026)
This community service program aimed to strengthen teachers’ capacity to manage AI-supported mathematics instruction through a modern educational administration approach. The program was conducted at SMPS Darul Ulum Tanoh Mirah and involved 18 teachers. It addressed teachers’ limited competence in integrating Artificial Intelligence into instructional planning, assessment, learning-media development, and administrative tasks. The activities comprised needs assessment, training, mentoring, hands-on practice, and evaluation through lectures, discussions, simulations, pre-tests, post-tests, Likert-scale questionnaires, and classroom implementation observations. The teachers were trained to use ChatGPT to develop teaching materials and lesson plans, AI-assisted digital quiz platforms to conduct assessments, and AI-supported design applications to create learning media. The results showed that the participants’ mean score increased from 65.3 on the pre-test to 84.7 on the post-test, representing an improvement of 19.4 points or 29.7%. The questionnaire results also indicated very high participant ratings, with the usefulness of the program and participant satisfaction each receiving a mean score of 4.6 out of 5. In addition, the teachers demonstrated improved ability to design technology-supported instructional materials, conduct digital assessments, and use student learning data for basic instructional decision-making. These findings indicate that structured AI training and mentoring can effectively enhance teachers’ professional competence and support more efficient, data-informed mathematics learning management.